Comparison of crude soluble antigen (CSA)- elisa and excretory secretory antigen (ESA)- elisa for serodiagnosis of invasive amoebiasis in selected orang asli serum samples - Salim, Muhammad Syahmii Mohamed (Universiti Sains Malaysia, 2017)
Amoebiasis is an infection caused by protozoan parasite Entamoeba histolytica which is responsible for about 100,000 deaths per year and it is the second leading cause of death due to protozoan parasites after malaria. Invasive amoebiasis can be categorized into either intestinal amoebiasis or extraintestinal amoebiasis, and the most common manifestation of invasive amoebiasis is amoebic liver abscess (ALA). At Hospital Universiti Sains Malaysia (Hospital USM), diagnosis of ALA relies on a combination of clinical findings, ultrasound examination of the liver and serodiagnosis using commercial kit such as indirect hemagglutination assay (IHA) technique. ELISA is a quantitative, routine laboratory assay which is simple to perform, sensitive and reliable. CSA is widely used in ELISA for serodiagnosis of ALA and also in commercial IHA test kit, while ESA was reported to be highly sensitive in recent studies. In this preliminary study, we compared CSA-ELISA and ESA-ELISA in relation to the standard commercial IHA test. Prior to performing ELISA, we screened selected Orang Asli serum samples by IHA with cutoff at 1:256 and obtained 33 positive samples and 30 negative samples. Based on the cutoff value of mean optical density + 2SD, CSA-ELISA showed 90.9% positive agreement (sensitivity), while ESA ELISA only showed 60.6% positive agreement. In contrast, both CSA-ELISA and ESAELISA showed over 96% negative agreement (specificity).